Tujuan Temu Kembali Arsip menggunakan Program Natadok di Kantor Arsip dan Perpustakaan Kota Payakumbuh - Mikel, Sepria; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This article aims to depict or describe the archive retrieval process using Natadok program in the Office of Archives and Library Payakumbuh. Data were collected through observation or interviews and literature associated with using descriptive research method which describe or explain the process of the ongoing events during the study. Based on analyzing the data, it can be concluded that the archive retrieval process using Natadok program at the Office of Archives and Library Payakumbuh as follows: 1) open Natadok app and login using the username and password that has been determined; 2) create a new cabinet or rack if the inputted document archive or no connection with the previous archives; 3) enter new documents; 4) retrieval of records or documents that have been inputted by clicking the edit menu and select retrieval or retrieval by keyword. Problems were found in the archive retrieval process using Natadok program at the Office of Archives and Library Payakumbuh The program is imperfect in the sense Natadok frequent application errors and lack of socialization of the use Natadok program. Efforts are being made to overcome the obstacles in the archive retrieval process using Natadok program at the Office of Archives and Library Payakumbuh that updating to the latest version of the program in order to avoid further program errors.Keyword: Review, Archive, Program Natadok